2016
DOI: 10.1007/s00405-016-4086-2
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcome of ion beam therapy in eight patients with head and neck cancers

Abstract: Ion beam therapy has enabled us to treat formerly untreatable malignant tumors. The aim of the present study was to investigate the long-term follow-up course of patients with head and neck cancers who received ion beam therapy. The subjects were 8 patients (3 men and 5 women aged 43-78 years) with head and neck cancers who visited our department from 2006 to 2015 and received ion beam therapy. Six patients received carbon ion beam therapy, and the other two patients received proton beam therapy. The medical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Seven of the eight CIRT cohorts covering 99.4% of the CIRT‐treated population reported acute grade 3‐5 AER. Only one case series of five patients did not report AER 12 . The rates were substantially lower in the PRT group (11/20 cohorts, 45.6% of the population) and the IMRT group (12/21 cohorts, 75.8% of the population).…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Seven of the eight CIRT cohorts covering 99.4% of the CIRT‐treated population reported acute grade 3‐5 AER. Only one case series of five patients did not report AER 12 . The rates were substantially lower in the PRT group (11/20 cohorts, 45.6% of the population) and the IMRT group (12/21 cohorts, 75.8% of the population).…”
Section: Resultsmentioning
confidence: 93%
“…Forty‐four (44) eligible studies (7 carbon ion, 11‐16 16 proton, 17,18,24,28,30‐41 and 21 IMRT 5‐7,42‐59 ) including the unpublished online data from our hospital 20 were identified from the database (see Figure 1). A representative sample of 2282 real‐world patients from 49 cohorts (8 CIRT cohorts, 20 PRT cohorts, and 21 IMRT cohorts) was included.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that tissue damage after carbon ion therapy appears more frequently, is more severe, and lasts longer than after proton therapy; this seems due to the higher relative biological efficacy (RBE) of carbon ions compared to protons [29].…”
Section: Pathophysiologymentioning
confidence: 99%